ElectionGuard: a Cryptographic Toolkit to Enable Verifiable Elections - Benaloh, Josh; Naehrig, Michael; Pereira, Olivier; Wallach, D. (USENIX Security, 2024)
,ElectionGuard is a flexible set of open-source tools that—when used with traditional election systems—can produce end-to-end verifiable elections whose integrity can be verified by observers, candidates, media, and even voters themselves. ElectionGuard has been integrated into a variety of systems and used in actual public U.S. elections in Wisconsin, California, Idaho, Utah, and Maryland as well as in caucus elections in the U.S. Congress. It has also been used for civic voting in the Paris suburb of Neuilly-sur-Seine and for an online election by a Switzerland/Denmark-based organization. The principal innovation of ElectionGuard is the separation of the cryptographic tools from the core mechanics and user interfaces of voting systems. This separation allows the cryptography to be designed and built by security experts without having to re-invent and replace the existing infrastructure. Indeed, in its preferred deployment, ElectionGuard does not replace the existing vote counting infrastructure but instead runs alongside and produces its own independently-verifiable tallies. Although much of the cryptography in ElectionGuard is, by design, not novel, some significant innovations are introduced which greatly simplify the process of verification. This paper describes the design of ElectionGuard, its innovations, and many of the learnings from its implementation and growing number of real-world deployments.